2021
DOI: 10.1080/07853890.2021.1875137
|View full text |Cite
|
Sign up to set email alerts
|

Association between apnea-hypopnea index and coronary artery calcification: a systematic review and meta-analysis

Abstract: Background The present study aimed to evaluate the association between presence and severity of obstructive sleep apnoea (OSA) and the presence of subclinical coronary artery disease (CAD) as assessed by coronary calcium score. Methods Medline, Cochrane, and Google Scholar databases were searched. The presence of coronary artery calcification (CAC) and CAC score were assessed. Results Irrespective of the cut-off value of apnoea-hypopnea index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…In a meta-analysis, Hao et al, showed an association between OSA and the presence of atherosclerotic lesions in patients without symptoms of heart disease. Furthermore, in a pairwise comparison, they indicated that the CACS might depend on the severity of OSA, which corresponds to our results [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…In a meta-analysis, Hao et al, showed an association between OSA and the presence of atherosclerotic lesions in patients without symptoms of heart disease. Furthermore, in a pairwise comparison, they indicated that the CACS might depend on the severity of OSA, which corresponds to our results [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…Besides hypertension, OSA plays a significant risk factor in other CVDs. The studies by Heilbrunn ES et al [ 12 ] and Hao W et al [ 13 ] are particularly notable for highlighting the impact of OSA on an elevated risk of cardiovascular mortality, as well as coronary artery calcification (CAC). This is in accordance with the 2005 retrospective study, which stated that the relative risk of sudden cardiac death (SCD) was 2.57-fold higher between midnight and 6 a.m. in patients with OSA compared with the general population.…”
Section: Reviewmentioning
confidence: 99%
“…In a meta-analysis, OSA has been found to independently increase the risk of subclinical CAD as measured by coronary artery calcification score [ 57 ]. Likewise, OSA was found to be an independent predictor of atherosclerotic plaque progression and vulnerability [ 58 ].…”
Section: Clinical Comorbidities Associated With Osamentioning
confidence: 99%